Inovasi Pembelajaran IPS Kelas VI Materi Kegiatan Ekonomi di Negara ASEAN Melalui Penerapan Model Problem Based Learning - Titi Agustinah; Chandra Wiwit Rahayu; Indri Kusuma Wardani; Heri Maria Zulfiati (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Learning innovation is something that is important and must be owned by teachers. The teacher's willingness to try, discover, explore and search for various learning approaches, methods and strategies is one of the supports for the emergence of various new innovations. Social studies as a subject at elementary school level is essentially a complete integration of social science disciplines and other relevant scientific disciplines to realize educational goals at school level. From the results of teacher observations, several problems were found in social studies learning, including: (1) in the teaching process teachers only use lecture and question and answer methods so that students tend to get bored because they find learning less interesting; (2) the learning that takes place is always teacher-centered so that student involvement is less active; (3) students' understanding and memory are still minimal. To overcome problems in learning in class VI, learning is implemented at SD Negeri Temon using the Problem Based Learning (PBL) method regarding Economic Activities in ASEAN Countries. The choice of the Problem Based Learning (PBL) method in the learning process is adjusted to the basic competencies in social studies learning. The teacher gives a number of trigger problems, then students continuously develop their knowledge in groups and individually.